Misuse of Pediatric Medications and Parent-Physician Communication: An Interactive Voice Response Intervention. Issue 3 (22nd April 2021) - Walsh, Kathleen E.; Bacic, Janine; Phillips, Barrett D.; Adams, William G.
Abstract : Background: Children take 1 medication each week on average at home. Better communication between parents and providers could support safer home medication use and prevent misuse of pediatric medications, such as intentional underdosing or overdosing. Our primary objective was to assess the impact of an interactive voice response system on parent-provider communication about medications. Methods: Parents of children 4 months to 11 years of age with upcoming well child visits were invited to call our interactive voice response system, called Personal Health Partner (PHP), which asked questions about the child's health and medication use. Responding parents were randomized to either PHP (interview and counseling) or control (injury prevention survey). Parents' responses were embedded in the electronic health record. After the physical visit, research assistants performed a phone follow-up survey. Results: Of 475 parents, including 293 PHPs and 182 controls, 93% were women. We found a high prevalence of misuse of medications: 14% reported underdosing (n = 63) fever-reducer medications and 3% reported overdosing (n = 13). Twenty percent (n = 37) of the 190 children younger than 3 years had received cold medication. Thirty-three percent (n = 19) of 62 PHP parents of children on prescription medications reported nonadherence. Among children on prescription medications, PHP significantly increased discussion of medications at the physical, but not the number who brought medications to the visit; it had no impact on those not on prescription medications. Conclusions: Pediatric medication misuse was common in this study. Use of a previsit interactive voice response system increased medication-related communication during visits and supports the need for systems that better prepare patients for visits and improve medication-related patient-physician communication.